On the Question of the Formation of a General Civil Identity - V. V. Gushch (Управленческое консультирование)
This article is devoted to the formation of the General civil identity of a multinational Russian society. The article analyzes a set of factors that influence the formation of a common civil identity and the solidarization of society based on the ideas that underlie the formation of the code of supranational cultural integrity.According to the author, supranational civil identity is the source of the meaning underlying the construction of a single supranational political nation. The General civil identity, being a tool of “soft power”, will allow the Russian state to strengthen its position in the information struggle for the formation of ideological trends that influence the foundations of a consensus dialogue, which will allow resolving a set of negative phenomena that prevent the formation of a unified national identity of citizens.